eGFR and creatinine clearance in renal failure - therapeutic decisions - Marta Bilska; Grzegorz Grześk (Polish Pharmaceutical Society, 2020)
Chronic kidney disease is the second most common chronic disease in Poland. Currently, about 4.2 million people suffer from it. When treating these patients it should be remembered that drugs that are eliminated mainly by the kidneys require dose adjustment depending on the severity of the kidney disease. There are also drugs that cannot be used in patients with renal insufficiency. The decisions about undertaking specific pharmacotherapy depend on the current results of laboratory tests showing the condition of the kidneys. Their correct interpretation ensures the effectiveness and safety of the applied treatment. Pharmacotherapy and choosing the correct dose in patients with renal failure is a serious therapeutic problem. For safe and effective pharmacotherapy, particular attention should be paid to the estimated patient glomerular filtration rate. It can be calculated by knowing the serum creatinine concentration based on appropriate mathematical formulas, e.g. MDRD or the newer CKD-EPI. In some laboratories, the estimated glomerular filtration rate is calculated automatically. To use these formulas, knowledge of serum creatinine, age, gender, and race are required. The values obtained on the basis of these two formulas may differ from each other in individual cases. The result can be used to determine the stage of chronic renal failure in a patient. Unfortunately, based on the estimated glomerular filtration rate automatically generated by laboratories, an incorrect therapeutic decision can be made without a careful analysis of the patient's clinical condition and assessment of factors that may have influenced the result. Assessment of kidney health based on estimated glomerular filtration rate is based on measured serum creatinine. Its level depends not only on the condition of the kidneys. The concentration changes under the influence of many factors: dehydration, diet, exercise, medications used. It also depends on age, gender and muscle mass. Hence, an overall assessment of the patient's clinical condition is important in this case. When some drugs are used in patients with renal insufficiency, lower doses or longer intervals between administrations are necessary. The information about the possibility of prescribing can be found in the Summary of Product Characteristics. When selecting the dose of the drug, the value of creatinine clearance calculated using the Cockcroft-Gault formula should be used. The Summary of Product Characteristics describes ranges for creatinine clearance values for which dose modification or discontinuation is required. Follow them to avoid any adverse drug reaction or drug toxicity.